Framework for the implementation & integration of ERP-MES system : a case study of an industrial process - Morakinyo, Samuel (2016)
This master thesis research study presents the case of an industrial production process that is embarking on enterprise system implementation and integration of ERP & MES system. A decision based on the need to meet internal & external demands for organizational change. This research study presented IT as a tool for enterprise system implementations and conceptual backgrounds from the business process and business architectural dimension, which set a roadmap towards the constructed framework for the implementation & integration project, specifically the implementation & Integration of ERP-MES system building on the framework presented in TOGAF. This research explored the functionalities and similarities of these systems to be implemented. A parallel case study was presented for prediction of the possible outcome of this research study. The theoretical and practical concepts considered relevant to this research objective were empirically tested and validated using the guidelines provided. The final framework for the implementation & integration of ERP & MES as presented in this research is the outcome of the rigor from previous effort with the effort from this research study, which is subject to further development and optimization for research purposes in organization’s general and case specific needs.